Euphrasia hirtella Jord. ex Reut. (Orobanchaceae) в Україні - Перегрим, О.М. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Критически анализируя образцы в гербариях KW и CHER мы выявили вид E. hirtella с территории Львовской и Хмельницкой областей. Предыдущие указания этого вида для территории Украины были ошибочными. Приводятся морфологическое описание и общий ареал вида. As a result of critical analysis of herbarium specimens in KW and CHER herbaria, specimens of E. hirtella collected in Lviv and Khmelnitsky regions have been revealed. Previous reports of this species for the territory of Ukraine have been proved to be erroneous. A morphological description and general range of the species are provided.